PARTISIPASI MAHASISWA DALAM PEMILIHAN RAYA DEWAN PERWAKILAN MAHASISWA (DPM) TINGKAT UNIVERSITAS PERIODE 2017/2018 DI KAMPUS FISIP UNIVERSITAS RIAU - Fitria Wulan Dari; Mita Rosaliza (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This research was carried out and political science University of Riau the campus. The purpose of this research is to know the student’s participation in general election of University seen from DPM political awareness of college student’s, and University benefits DPM function in the presence of intra-campus organization’s. The method used in this research is using descriptive quantitative approach uses, with total of 98 respondent’s students in political science, which determined through proportional sampling technique. Data analysis was done using cross tabulation analysis through SPSS program. The result showed that the level of political awareness of college student’s in the pemira DPM University level on the campus of the Universitas Riau, seen at the time of registrstion, the election compaign, and the general election was still low a total of 95,9% of respondents. The results of this research also look that university have the DPM function in institutional, one of the function of DPM is to accommodate and accept the aspirations of students, and this function has been carried out by members of the DPM. As an organization of intra-campus university DPM has benefits for the betterment of the university, so that the benefits of this organization has been felt by students although not all students who feel its benefits. Because, the term of office in this organization for just one year, while for the realization of the aspirations of all student need a fairly long time. So, with this short term not yet seen all of the results submitted by the students aspirations.Keywords: Political Participation, Students, General Election DPM University